Genome Sequencing for Cases Unsolved by Exome Sequencing: Identifying a Single-Exon Deletion in TBCK in a Case from 30 Years Ago - Jacob, Maureen; Brugger, Melanie; Andres, Stephanie; Wagner, Matias; Graf, Elisabeth; Berutti, Riccardo; Tilch, Erik; Pavlov, Martin; Mayerhanser, Katharina; Hoefele, Julia; Meitinger, Thomas; Winkelmann, Juliane; Brunet, Theresa (Neuropediatrics, 2024)
In patients with neurodevelopmental disorders (NDDs), exome sequencing (ES), the diagnostic gold standard, reveals an underlying monogenic condition in only approximately 40% of cases. We report the case of a female patient with profound NDD who died 30 years ago at the age of 3 years and for whom genome sequencing (GS) now identified a single-exon deletion in TBCK previously missed by ExomeDepth, the copy number variation (CNV) detection algorithm in ES.Deoxyribonucleic acid (DNA) was extracted from frozen muscle tissue of the index patient and the parents' blood. Genome data were analyzed for structural variants and single nucleotide variants (SUVs)/indels as part of the Bavarian Genomes consortium project.Biallelic variants in TBCK, which are linked to the autosomal recessive disorder TBCK syndrome, were detected in the affected individual: a novel frameshift variant and a deletion of exon 23, previously established as common but underrecognized pathogenic variant in individuals with TBCK syndrome. While in the foregoing ES analysis, calling algorithms for (SNVs)/indels were able to identify the frameshift variant, ExomeDepth failed to call the intragenic deletion.Our case illustrates the added value of GS for the detection of single-exon deletions for which calling from ES data remains challenging and confirms that the deletion of exon 23 in TBCK may be underdiagnosed in patients with NDDs. Furthermore, it shows the importance of “molecular or genetic autopsy” allowing genetic risk counseling for family members as well as the end of a diagnostic odyssey of 30 years.
Keywords: TBCK; genome sequencing; molecular autopsy; neurodevelopmental disorder